Antioxidant capacity of Melissa Officinalis L. on Biological Systems - Franco, Juliana Metzner; Pugine, Silvana Marina Piccoli; Scatoline, Antônio Márcio; de Melo, Mariza Pires (Eclética Química, 2018)
The aim of the present study was to evaluate in vitro antioxidant capacity of Melissa extract (ME) (Melissa officinalis L.) and its protective effect on peroxyl radical-induced oxidative damage in erythrocytes. ME used in present study was obtained by rota-evaporation of the crude extract (ethanol:water/dried leaves). Total phenolic and flavonoids contend determination, 176.8 ± 13.2 mg GAE/g dw and 26.2 ± 3.2 mg QE/g dw, respectively). Total equivalent antioxidant activities, TEAC in mg TE/g dw, were 61.4 ± 5.5 and 512.4 ± 77.2 for respective FRAP assay and DPPH• radical-scavenging. The ME acts as an antioxidant on NO and O2•-, when ME exerted a higher antioxidant action on NO scavenging to compared to the ascorbic acid (1.9 times), however, the antioxidant capacity of ME on O2•- was lower than ascorbic acid (5.6 times). The values of hemolysis inhibition from ME (IC50, 2.0 ± 0.5 mg/mL) were higher than ascorbic acid (IC50, 7.1 ± 1.8 mg/mL). Extract of Melissa was able to eliminate biological free radicals, suggesting a potential to prevent oxidative damage in vivo. In fact, the ME exerted protective action on cell membrane lysis in situ.